Anatomic Variation of Posterior Slope of Tibial Plateau in Adults - Humagain, Vaskar; Maharjan, Rajram; Paudel, Krishna P; Sigdel, Arun; Sah, Krishna J; Regmi, Rabindra (Journal of Institute of Medicine Nepal, 2021)
Introduction Posterior tibial slope (PTS) is the tilt bore by the tibial plateau posteriorly and inferiorly relative to the long axis of the shaft of tibia. Mean PTS in each population is imperative to keep within the normal range as possible for good outcome of different surgeries around the knee. Measurement of the PTS using plain radiograph is a cost effective, facile approach and can be done without the use of advanced imaging modalities. Methods A prospective observational study was done from January to December 2020. Patients presenting to Outpatient Department (OPD) at National Trauma Center, NAMS with minor knee problems like soft tissue injury, pain, and stiffness were included in the study. PTS was measured via software on a true lateral radiograph of affected knee and its mean value was correlated with parameters, namely, age, sex, BMI, laterality, and race. Results Mean PTS was 10.350 ±2.030 (range 3-140) in the study size of 185. The mean age of study population was 41.25 ± 15 years (range: 19-73 years). There were 96 males and 89 females in the study. Mean PTS in males was 10.650±2.040 while that in females was 10.030±1.970. The mean BMI of individuals in this study was 25.3 ± 2.61 kg/m2. There was no statistically significant correlation of PTS with age, sex, BMI, laterality, and ethnicity. Conclusion Posterior tibial slope in adults is not influenced by sex, BMI, side, ethnicity or advancing age.